THE USE OF STORYTELLING METHOD TO IMPROVE STUDENTS' ABILITY IN WRITING STORIES AND TEACHER’S ABILITY IN TELLING STORIES - Ana Widyastuti (Universitas Indraprasta PGRI, 2019)
Abstract: This study is to improve children's story writing skills and to tell stories using the method of attracting kindergarten teachers in Depok city. This research is a form of methods classroom action research. The research subjects are kindergarten teacher in Limo and Cinere sub-district is 20 people.The research object is children's story writing skill and teacher performance telling story with interesting method of creative media. Data collection method using method of test, observation, and documentation Data analysis technique that is quantitative and qualitative technique by finding the average value of teacher's story The result of this research show that this can improve children's story writing skill and teacher story.The improvement of writing this story is: the story material of children, linguistic material, how to write stories, techniques and methods of interesting storytelling.The improvement is shown by the average value of children's story writing skills.A pre cycle from 41.55 to 53.35, an increase of 12.2.Cycle II to 79, an increase of 25.5 The ability to tell a story is indicated by the average pre-siklus value 50.05 to 62.3, an increase of 12.25. While the second cycle became 80.10, the increase to 17.8. Keywords: writing children story, story telling method, telling kindergarten teacher